Under-Developed Standards: The Reality in an Elderly Facility - Padayao, Maria Flordeliz; Guazon, Cielito; Bacarro Apuhin, Mercy Milagros; Cabatana, Ma. Estella (JPAIR Multidisciplinary Research, 2017)
The burgeoning population of the elderly is an alarm that the national health and nursing authorities should start equipping to meet the needs of this fragile group. The Philippines is still under-developed in the standardization of geriatric institutions. Mainly, the objective of this study is to evaluate whether the selected elderly home in Cebu City, Philippines is practicing a quality facility structuring based on guidelines. A mixed method, specifically, the Sequential Explanatory research, was used to understand the complexities of this phenomenon. Using a multi-level of data sourcing, a meticulous sequencing was followed. First, employing a survey questionnaire; then, an observational checklist and lastly, a cross analysis Focus Group Discussion (FGD). To complete the different sets of sample, an active purposive sampling technique was utilized. Findings showed that lack of national standards and financial incapability were the identified factors why there was a non-parallelism between the elderly needs and conduciveness of quality living. As such, may threaten the holistic health and harmony of well-being among them. The result can be applied as reference in generating a standardized protocol suitable for Filipino aging clientele.